Ultra-violet C absorption and LPG sensing study of zinc sulphide nanoparticles deposited by a flame-assisted spray pyrolysis method. Issue 3 (1st July 2016) - Nemade, K.R.; Waghuley, S.A.
Abstract: Solvent processed spray pyrolysis is a technique that has attracted worldwide interest for the synthesis of nanoparticles. Zinc sulphide (ZnS) belongs to a category of practical semiconductors known as metal sulphides, and it is used extensively as an optical material. In the present article, ZnS nanoparticles were successfully synthesized using flame-assisted spray pyrolysis. X-ray diffraction confirmed the formation of ZnS with an excellent crystalline structure, while scanning electron microscopy indicated that the as-synthesized materials were nanoparticles. Ultraviolet–visible spectroscopy was utilized to evaluate the optical property of the resulting product and revealed that ZnS nanoparticles have the capacity to absorb ultra-violet C. In addition, various liquefied petroleum gas (LPG) sensing properties of the ZnS nanoparticles were also evaluated.